Synergistic effects of total ionizing dose on single event upset sensitivity in static random access memory under proton irradiation - 肖尧 郭红霞 张凤祁 赵雯 王燕萍 张科营 丁李利 范雪 罗尹虹 王园明 (Chinese physics B, 2014)
Synergistic effects of the total ionizing dose （TID） on the single event upset （SEU） sensitivity in static random access memories （SRAMs） were studied by using protons. The total dose was cumulated with high flux protons during the TID exposure, and the SEU cross section was tested with low flux protons at several cumulated dose steps. Because of the radiation-induced off-state leakage current increase of the CMOS transistors, the noise margin became asymmetric and the memory imprint effect was observed.